INFLUENCE OF BENZYL ADENINE, ADDITION OF ORGANIC FERTILIZERS AND THINNING ON SOME PHYSICAL AND CHEMICAL PROPERTIES OF DATE PALM CV. MEJHOUL - Hisham A. Mansour; AL-Dahan, M. R. Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to determine effect of foliar application of growth regulator benzyl adenine, adding organic fertilizers and thinning on some physical and chemical properties of date palm fruits Cv. Mejhoul, The experiment was carried out according to a randomized complete block design with three replicates and three factors: foliar application of benzyl adenine at concentrations (0, 100, 150 mg L-1) and symbolized B0, B1, B2, and adding organic fertilizer at levels (0, 1 kg humic acid + 150  g seaweed extract for every tree, 2 kg humic acid + 300 g seaweed extract for every tree) symbols F0, F1, F2 and thinning at two levels (without thinning, removing 10 cm from tips of flower spikes and removing central area of branching from peduncle) symbols T0, T1 and included 54 experimental units, results showed superior treatment B2 increasing average fruit weight, fruit flesh weight, seed weight, and percentage of total, reducing, and non-reducing sugars, 30.82 g, 28.95 g, 1.80 g, 63%, 58.38%, and 4.62%, respectively. Treatment F2 gave highest average fruit weight, flesh weight, seed weight, total and reduced sugars, 29.16 g, 27.42 g, 1.76 g, 59.75%, 55.30%, respectively. Treatment T1 was significantly superior in increasing fruit weight, fruit flesh weight, seed weight, and percentage of total, reduced and non-reduced sugars, with values 31.80 g, 30.06 g, 1.75 g, 63.31%, 58.81%, 4.49%. T1 B2 F2 interaction had the highest average fruit weight, fruit flesh weight, seed weight, and percentage of total and reducing sugars. with values of 36.68 g, 34.46 g, 2.21 g, 72.55%, and 67.97%, respectively.